Barriers, facilitators, preferences and expectations of joint protection programmes for patients with hand arthritis: a cross-sectional survey. Issue 1 (22nd January 2021) - Bobos, Pavlos; MacDermid, Joy; Ziebart, Christina; Boutsikari, Eleni; Lalone, Emily; Ferreira, Louis; Grewal, Ruby
Abstract : Objectives: The objective of this survey was to investigate the barriers, facilitators, expectations and patient preferences regarding joint protection (JP) programmes in people with hand arthritis. Design: Cross-sectional survey. Setting: Tertiary clinic. Participants: Patients with hand arthritis: osteoarthritis, rheumatoid arthritis, psoriatic arthritis and other forms of arthritis. Primary and secondary outcome measures: This study used a survey among people with hand arthritis. Descriptive statistics and percentages were reported for all the data about the barriers, facilitators and preferences around JP. Results: A total of 192 patients consented to participate. Most of the patients (82%) were unaware of JP. Factors that may act as barriers to participation and were regarded as 'a very big concern' were: cost of the programme (44%), time of offering the programme (39%), work commitments (36%) and having a centre/clinic close to the house (28%). Factors that may act as facilitators and rated as 'extremely helpful' were: research that shows that JP works (26%) and having the centre/clinic close to the house (25%). An online format for JP was the most preferred option (54%). Half (46%) preferred a timeframe of 1 hour, three times per week and 44% preferred a 2-hour programme, for three times per week. Conclusions: Awareness of the potential benefits of JP, and prior experience with JP programme were very low. Common potentially modifiable patient-reported barriers to participate in future JP interventions, included: cost, work commitments, distance from home to clinic and times that the intervention were provided. These barriers might be addressed with free and accessible forms of delivery of JP, which may lead to better uptake and participation in JP programmes.